THE DISCOURSE OF WELFARE STATE, SOCIAL JUSTICE AND REALITY IN NEW ORDER POST, INDONESIA: PREMILINARY NOTES FROM THE RELATION BETWEEN STATE AND SOCIETY 2000-2009 - Herdi Sahrasad (Universitas Islam Negeri Alauddin Makassar, 2018)
This paper discusses the discourse welfare state or social state as well as the social justice. The state is formed on motivating citizen consensus or social contracts that are associated with resolving problems that cannot be solved individually such as justice, welfare, law enforcement, eradicating corruption-collusion-cronyism, prosperity distribution, security and so forth. Indonesia post New Order trying to find a solution to the political-economic crisis that hit and the intelligentsia here proposes various ideas and ideas to develop the country and nation in accordance with the aspirations and development of their society. In this case, the citizens' request or invitation to the state to be involved in solving problems and challenges that cannot be solved by the community is called the principle of subsidiarity. Of course, outside the needs of the community,